2014
DOI: 10.1126/science.1257258
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking China's new great wall

Abstract: Massive seawall construction in coastal wetlands threatens biodiversity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
349
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 471 publications
(351 citation statements)
references
References 7 publications
1
349
0
1
Order By: Relevance
“…Waterbird populations are declining globally (Hansen, Menkhorst, Moloney, & Loyn, 2015;Z. Ma et al, 2014;W.…”
Section: Introductionmentioning
confidence: 99%
“…Waterbird populations are declining globally (Hansen, Menkhorst, Moloney, & Loyn, 2015;Z. Ma et al, 2014;W.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, approximately 80 % of coral reefs and mangrove swamps have disappeared, and 57 % of wetlands have shrunk since the 1950s in China's coastal areas (Hughes et al 2013;Murray et al 2014). Adverse socio-economic and ecological consequences of overexploitation of coastal ecosystem have already emerged (Ma et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Coastal wetlands along China's Yellow Sea coast are in crisis (MacKinnon et al 2012;Ma et al 2014) and the tidal flats have been identified as an endangered ecosystem under IUCN criteria . Murray et al (2014) estimate the area of China's tidal flats were~5398 km 2 in the 1950s,~2677 km 2 in the 1980s and, by the 2000s, had decreased to 1611 km 2 , with the average annual rate of loss since the 1980s being 1.8% per annum (p.a.)…”
Section: Introductionmentioning
confidence: 99%